Prospects of Renewable Energy at Rural Areas in Bangladesh: Policy Analysis - Kabir, KMH; Uddin, MK (Journal of Environmental Science and Natural Resources, 2015)
Presently the country faces a peak load shortage of 30% of total demand and the shortage of gas supply resulting in about 10% of power plants leaving idle. It also reveals that about 1-2% GDP growth declined annually owing to the shortage of energy and poorer ability of power generation. The present study seeks to analyze the issues and challenges of renewable energy (RE) in Bangladesh with special emphasis on prospects of energy generation at rural areas of Bangladesh and subsequent policy analyses. Electricity generation through RE and implementation of energy efficiency and conservation including the RE policies and their analyses will explore to meet the future unmet demand in power sector. Lessening of dependency on natural gas is one of the top agenda of the government, in addition Bangladesh has enormous prospects of RE (solar energy) to meet the unmet demand particularly at the remote and off grid areas. By this time, the government of Bangladesh has planned to generate 5% of generation (i.e., 800MW) by 2015 and subsequently 10% (i.e., 2000MW) by 2020 from renewable sources and 20% of total generation by nuclear, renewable and cross border by 2030 out of40,000 MW total expected generations. In this paper possible attempts have been made to identify the problems and prospects related to the RE particularly for solar energy at rural areas and their possible recommendations for future development towards achieving millennium goal. J. Environ. Sci. & Natural Resources, 8(1): 105-113 2015